Pengaruh Penggunaan Brain Based Learning Berbantuan Wordwall terhadap Keterampilan Proses Sains dan Hasil Belajar Siswa - Adzilla, Rosita Aulia; Herliani, Herliani; Rambitan, Vandalita Magdalena Maria; Masitah, Masitah; Akhmad, Akhmad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Brain Based Learning is an approach based on how the human brain works. This model creates a learning atmosphere that is in harmony with the way the brain naturally processes information, with the hope of increasing student participation and their learning outcomes. In its implementation, the Brain Based Learning model is combined with the use of Wordwalls as a learning aid. Wordwall is a technology-based platform that offers a variety of user-friendly quizzes, games, and activities. This study aims to determine the effect of the use of the Brain Based Learning model and Wordwalls on science process skills and student learning outcomes. This type of research is a quasi-experimental study using a Pretest-Posttest Control Group Design. The research instrument uses a test, with 10 essay questions, 5 questions to measure science process skills, and 5 questions to measure student learning outcomes. The sampling technique in this study uses the Purposive Sampling technique. To analyze the data, the researcher used the t-test with a significance level of 0.05. The results of the analysis show that the t-test obtained a sig. A 2-tailed test of 0.00 (0.00<0.05) for both variables indicates an effect of the Brain-Based Learning model assisted by Wordwall media on the science process skills and learning outcomes of 11th-grade students at SMA Negeri 13 Samarinda on the human sensory system topic.